Water security: A review of place-based research. Issue 82 (April 2018) - Gerlak, Andrea K.; House-Peters, Lily; Varady, Robert G.; Albrecht, Tamee; Zúñiga-Terán, Adriana; de Grenade, Rafael Routson; Cook, Christina; Scott, Christopher A.
Highlights: Our study reports a growing, diverse, and expansive body of place-based water security research. Diversity is found in the wide range of definitions and indicators and in expanding geographic coverage: more regions of the world are being studied, and at greater variety of spatial scales. Water quantity—specifically scarcity in relation to demand—remains a dominant framing of water security. The variability shown in our results underscores the importance of incorporating community context . Abstract: Water security has emerged as a major framing template in environmental governance and resource management. The term and underlying concepts have attracted the attention of governmental and nongovernmental organizations, private industry, and the academy in policy and practice. Notwithstanding the palpable rise in its use, a comprehensive understanding of how water security is conceptualized and employed in different contexts around the world is limited. We aim to address this gap, by assessing how water security is considered, articulated, and operationalized in place-based studies. We employ a two-part methodological approach that includes (1) a systematic analysis of 124 articles, books, and book chapters published between 2010-2015 using a standardized coding framework to examine trends and patterns in place-based water security research, and (2) an analysis of the treatment of governance as a subset of this body of research to reveal how water governance is framed and understood in place-based water security scholarship. We find broad diffusion of water security across geographic regions and scales, expansive framing of water security, and evolving approaches to indicator formulation. The narratives around future pathways for governance practices include the promotion of participatory processes, solutions that engage both quantitative and qualitative methods, and a mix of both hard- and soft-path approaches to achieve water security. The persistent diversity in perspectives and applications of water security suggests that scholars adapt the concept to the contexts of the cases they are studying. The variation in how water security is utilized in different regions and spatial scales underscores the importance of incorporating community context in how we understand and employ water security. By empirically assessing the diversity and utility of water-security analyses, highlighting regional differences, and tracing evolving conceptions over time, our research can inform future project design, policy-making, and management from the international to the local levels.